A Prevalence Of Low Back Pain Among Sewing Machine Operators - Firoj Kazi, Jabiulla; G. Varadharajulu, G. Varadharajulu (Journal of Neonatal Surgery, 2025)
Background: A frequent musculoskeletal condition is low back pain, especially in workers who adopt extended or repetitive postures. Because of the nature of their employment, which sometimes entails prolonged sitting, repetitive motions, and perhaps poor ergonomics, sewing machine operators are among such group that frequently faces the exposure of getting back injuries. Over the day, sewing machine operators engage in repetitious, repetitive elbow, wrist, and finger movements while doing laborious tasks at a rapid work rhythm. In addition to individual factors like age, experience, and physical fitness that further influenced the probability of musculoskeletal discomfort and LBP, prolonged repetitive jobs, poor ergonomics, and insufficient rest intervals exacerbated strain. Musculoskeletal pain symptoms increase workers' knowledge of their health by assisting them in identifying the type and severity of their pain. This knowledge encourages greater engagement at work, allowing people to successfully manage discomfort and sustain productivity while lowering the chance of developing new health issues. Ascertaining the prevalence of LBP among sewing machine workers was the aim of this study. Methods: This study is observational. was conducted on hundred People suffering from lower back pain in the population of sewing machine workers. The study was carried through using a questionnaire. The questionnaire included a number of questions about sewing machine operators' employment status and LBP symptoms. Result: 100 participants who participated in the study, of the sewing machine workers with LBP population. They answered a questionnaire. 73 (73%) individuals of the sewing machine users having high risk score for LBP while 27 (27%) participants had a low-risk score on the questionnaire. Conclusion: These results indicate that among sewing machine operators, the risk of low back pain is the crucial factor.